Ghost-arc geochemical anomaly at a spreading ridge caused by supersized flat subduction - Gianni, Guido Martin; Likerman, Jeremias; Navarrete Granzotto, César Rodrigo; Gianni, Conrado Rubén; Zlotnik, Sergio (Nature Communications)
The Southern Atlantic-Southwest Indian ridges (SASWIR) host mid-ocean ridge basalts with a residual subduction-related geochemical fingerprint (i.e., a ghost-arc signature) of unclear origin. Here, we show through an analysis of plate kinematic reconstructions and seismic tomography models that the SASWIR subduction-modified mantle source formed in the Jurassic close to the Georgia Islands slab (GI) and remained near-stationary in the mantle reference frame. In this analysis, the GI lies far inboard the Jurassic Patagonian-Antarctic Peninsula active margin. This was formerly attributed to a large-scale flat subduction event in the Late Triassic-Early Jurassic. We propose that during this flat slab stage, the subduction-modified mantle areas beneath the Mesozoic active margin and surrounding sutures zones may have been bulldozed inland by >2280 km. After the demise of the flat slab, this mantle anomaly remained near-stationary and was sampled by the Karoo mantle plume 183 Million years (Myr) ago and again since 55 Myr ago by the SASWIR. We refer to this process as asthenospheric anomaly telescoping. This study provides a hitherto unrecognized geodynamic effect of flat subduction, the viability of which we support through numerical modeling. Fil: Gianni, Guido Martin. Universidad Nacional de San Juan. Facultad de Ciencias Exactas, Físicas y Naturales. Instituto Geofísico Sismológico Volponi; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - San Juan; Argentina Fil: Likerman, Jeremias. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: Navarrete Granzotto, César Rodrigo. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina. Consejo Nacional de Investigaciones Científicas y ...